The Photographers [videorecording] - Bernanke, Jaime (The Society, 1995)
The video takes you around the world to meet the ten National Geographic photographers as they reflect on their jobs and on their art. An interview with these remarkable photographers on their secrets in the field, how they get those breathtaking shots, the dangers they face, and the lives they lead for the love of their craft.